The fascial system and exercise intolerance in patients with chronic heart failure: hypothesis of osteopathic treatment - Bordoni, Bruno (J Multidiscip Healthc, 2015)
Chronic heart failure is a progressive, debilitating disease, resulting in a decline in the quality of life of the patient and incurring very high social economic costs. Chronic heart failure is defined as the inability of the heart to meet the demands of oxygen from the peripheral area. It is a multi-aspect complex disease which impacts negatively on all of the body systems. Presently, there are no texts in the modern literature that associate the symptoms of exercise intolerance of the patient with a dysfunction of the fascial system. In the first part of this article, we will discuss the significance of the disease, its causes, and epidemiology. The second part will explain the pathological adaptations of the myofascial system. The last section will outline a possible osteopathic treatment for patients with heart failure in order to encourage research and improve the general curative approach for the patient.